Does Prevalence Mitigate Relevance? The Moderating Effect of Group-Level OCB on Employee Performance - Bommer, William H.; Dierdorff, Erich C.; Rubin, Robert S. (Academy of Management Journal, 2007)
This article explores multilevel relationships between group-level OCB, individual-level OCB, and work performance. We also discuss conceptualizing OCB with regard to context and multiple levels of analysis. We hypothesize that group-level OCB moderates the relationship between individual-level OCB and job performance. Results based on 100 work groups in a manufacturing firm indicate that group-level OCB significantly moderated the relationship between individual-level OCB and job performance. Comparing contexts in which group-level OCB was rare with those in which it was prevalent, we found that high individual-level OCB yielded greater significant increases in job performance ratings when group-level OCB was rare.